INFRASTRUCTURAL FEATURES OF KRIVYI RIG CITY AS AN ADDITIONAL FACTOR OF THE IMPACT OF AUTOMOBILE TRANSPORT ON THE ENVIRONMENT - HALAKTIONOV, MYKOLA; BREDUN, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The city of Kryvyi Rih is one of the centers of heavy industry with a high concentration of objects of the mining and metallurgical complex, which leads to negative consequences for the environment, while motor vehicles make a significant contribution to air pollution in the region. Every year, motor vehicle emissions increasingly affect the state of atmospheric air pollution in large cities, which becomes a very important factor in the deterioration of the quality of life of the population. As a result of the study, it was established that the transport infrastructure of Kryvyi Rih is very extensive and covers the entire territory of the city, the public transport of the city is represented by all types of transport to ensure urban, suburban and intercity transportation. Roads of regional and national importance pass through the city, intersecting with central streets and creating an additional impact on the environment. The increase in the number of motor vehicles leads to the loading of city highways, which leads to an even greater burden on the ecological situation in the city. The routes with the most intense traffic were determined, the configuration of the main junctions and intersections was determined, the intensity of pollutant emissions into the atmospheric air was calculated, road sections at regulated, non-regulated intersections and roundabouts were analyzed. Proposed recommendations for reducing impacts in these areas. The solution to the problem of the impact of motor vehicles is the implementation of comprehensive environmental protection measures, such as the emission monitoring system, the organization of traffic flows, and the introduction of environmentally friendly technologies. The development of ecological public transport and the development and popularization of bicycle infrastructure, which will contribute to the reduction of car traffic in the city center.